Sacral Topography of Late Antique and Early Christian Doclea (Montenegro): the First Modern Preliminary Investigation - Koprivica, Tatjana (Actual Problems of Theory and History of Art, 2025)
The subject matter of the present research is the architecture of Late Antique and Early Medieval Doclea in Dalmatia. The aim of the research is to establish new facts, by reviewing and reexamining past written records and research outcomes of archeological campaigns of 1954–1964, 1999 and 2005 respectively, as well as by reading recent writings concerning similar topics, in order to get a proportionate detailed image of the sacral topography of the city.
Keywords: Doclea; Dalmatia; Montenegro; late antique urban complex; early Medieval urban complex; sacral topography